Behaviour of holstein cows in robotic milking Comportamento de vacas da raça Holandesa em ordenha robotica - Cordova H.A. (2020)
© 2020 Universidade Federal de Minas Gerais.The aim of this study was to assess the ingestive behavior of concentrate and milking of dairy cows in automatic milking system (AMS) according to parity. The experiment was conducted from March to June 2014, in Castro, PR, with Holstein cows housed in a free stall, milked automatically, and classified according to the lactation order (1, 2 and +3 lactations). Data were extracted from the management software, considering the activities of one day a month (24 hours) for four months, the day after the official milk production control. The data were analyzed by multivariate analysis (factorial analysis, canonical and cluster), using the statistical package SAS. The ingestive behavior of concentrate influenced the entire activity of the cows in the AMS, being a fundamental factor in the performance of animals in this system. Parity did not influence the milking behavior, only the ingestive behavior, due to the social dominance of multiparous cows. High-yielding cows had a more aggressive ingestive behavior. It was concluded that parity influenced the ingestive behavior of concentrate, but does not interfere in milking behavior in cows with higher parity. In the AMS, primiparous should be managed in a specific group.